2010
DOI: 10.1111/j.1399-5618.2010.00882.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased peripheral blood expression of electron transport chain genes in bipolar depression

Abstract: Objective To identify specific genetic pathways showing altered expression in peripheral blood of depressed subjects with bipolar disorder (BPD). Methods Illumina Sentrix BeadChip (Human-6v2)microarrays containing > 48,000 transcript probes were used to measure levels of gene expression in peripheral blood from 20 depressed subjects with BPD and in 15 healthy control subjects. Quantitative real-time reverse transcription polymerase chain reaction (qRT-PCR) was used to confirm a subset of these differences. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 83 publications
(97 reference statements)
2
42
1
Order By: Relevance
“…Since mitochondrially formed oxidants activate several signaling pathways related to apoptosis [47], this GO term was associated with the differentially expressed genes identified in this comparison, as expected.…”
Section: Discussionmentioning
confidence: 69%
“…Since mitochondrially formed oxidants activate several signaling pathways related to apoptosis [47], this GO term was associated with the differentially expressed genes identified in this comparison, as expected.…”
Section: Discussionmentioning
confidence: 69%
“…Several studies have suggested that dysfunctional cellular energy metabolism has a central role in BD, mainly in the mitochondria (Beech et al, 2010;Maurer et al, 2009;Wang, 2007;Anglin et al, 2012). Abnormalities in energy metabolism were found in functional assays and in magnetic resonance spectroscopy studies (Dager et al, 2004;Deicken et al, 1995;Frey et al, 2007;Regenold et al, 2009).…”
Section: Introductionmentioning
confidence: 96%
“…Antipsychotic and mood stabilizer medication have a well known immunomodulatory effect [2629], which likely impacts peripheral gene expression, and thus it is uncertain whether the biomarker profiles identified largely reflect the response to medications. Two recent and important papers have moved towards addressing this issue [30,31]. In a study of major depressive disorder, Spijker et al, identified a lipopolysaccharide stimulated lymphocyte signature that could discriminate 21 unmedicated major depressive disorder patients from 21 controls, that was confirmed with 71.4% specificity and 76.9% sensitivity in a replication sample of 13 patients and 14 controls [30].…”
Section: Introductionmentioning
confidence: 99%